A WEBPAGE DEVELOPMENT OF ECOTOURISM DESTINATIONS IN A PHILIPPINE PROVINCE - Jennifer Reyes; Denmark Catan (Fakultas Pariwisata Universitas Pancasila, 2022)
The study aimed to create a website on the interesting places that travelers want to visit for leisure, business, and other related purposes within the province of Southern Luzon, Philippines. This contains gathered information on developing a webpage of ecotourism destinations in the province. This practical study was designed for ecotourists so they will have easy access to reading, locating, and experiencing the Quezon Province. This provides the necessary information that travelers and even students need in visiting a tourist destination which is considered the product information of each particular destination. This research employed analysis of the available data from the government offices, academic institutions, professional blogs, and responses gathered from online surveys participated by tourism students, travelers, residents, tourism office personnel, and local government officials to perform the profiling, designing, and developing the framework of this research and development study. As a result, the researchers developed a webpage as an output of this study. The appropriate design was based on the areas of usability, speed, aesthetics, contents, contact information, maintenance availability, and mobile-friendly features which are highly considered in this research project.